The Role and Value of Happiness in the Work of Paul Ricoeur - Verhoef Anné Hendrik (Open Philosophy, 2023)
The role and value of happiness in the work of Paul Ricoeur remains an understudied theme. It is especially Ricoeur’s unique dialectical understanding of happiness, unhappiness, and chance which brings a crucial and much-needed insight and correction with regard to the understanding of happiness in our contemporary culture. For Ricoeur, happiness is always in relation to unhappiness, and it appreciates chance within the striving–receiving tension that remains characteristic of happiness. This understanding of happiness provides an alternative to the destructive notions of happiness that leave us trapped in the hedonistic treadmill, the endless unsatiable desires of our existence, the narcistic satisfaction of our needs, and the infinite unhappy pursuit of happiness.